Topology Control Algorithm in Heterogeneous Wireless Sensor Network with Energy Supply - Chenming Ma; Wanliang Wang; Zhen Hong; Xinwei Yao (Dianxin kexue)
In view of the problem that current algorithm mainly research on topology construction or topology maintenance separately，a topology control algorithm based on two processes combined was proposed，which was adaptive to the network with heterogeneous communication and energy.Topology construction was to construct connected dominating set with low message overhead，and topology maintenance was to execute local or global repair strategies by sink node based on time，energy or failure mechanism to save energy.Theoretical analysis and simulation experiments confirm that the algorithm can construct topology with low time and message overhead and extend network lifetime.